ECONOMIC POLICY OF SULTAN AGENG TIRTAYASA IN THE IMPROVEMENT OF TRADE ECONOMY IN THE CULTURE OF BANTEN 1651-1682 AD - Siregar, Ahmad Rajab (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
During the reign of the fifth ruler of Banten, Sultan Ageng Tirtayasa, the Sultanate of Banten reached its era of glory. One of the factors that supported Sultan Ageng Tirtayasa's achievements was his economic trade policy. His policies were considered to be in conflict with his hatred towards one of the European nations, the Dutch. Sultan Ageng Tirtayasa disliked the Dutch for destroying Banten's political system and trying to monopolize trade. Based on the Dutch attitude towards Banten, Sultan Ageng Tirtayasa should have been more cautious towards foreigners. At the beginning of his reign, he reopened the free trade system and allowed foreigners to settle in Banten. The purpose of this study is to analyze the economic policy of Sultan Ageng Tirtayasa and its impact on the improvement of the trade economy in the Sultanate of Banten. This research is a literature study that uses literature as a source. This research is also classified as a type of descriptive research using the historical method. The references used in this research are sourced from various literatures, such as books, articles, and final assignments. The result of the analysis of this research is that the economic policy implemented by Sultan Ageng Tirtayasa was carried out by putting aside his worries about Europeans. The policy was implemented by reopening the free trade system, allowing the Chinese to settle in Banten, and building Chinatown. Sultan Ageng Tirtayasa's policy was able to increase revenue for the Sultanate of Banten. In addition, this policy made Banten's harbor more crowded by traders with more and more partners